Fishing for Litter in the Adriatic-Ionian macroregion (Mediterranean Sea): Strengths, weaknesses, opportunities and threats. (February 2019) - Ronchi, Francesca; Galgani, Francois; Binda, Flavia; Mandić, Milica; Peterlin, Monika; Tutman, Pero; Anastasopoulou, Aikaterini; Fortibuoni, Tomaso
Abstract: Marine litter represents a transboundary challenge since it originates from manifold sources and travels long distances. Reducing marine litter can involve measures to prevent, mitigate, and remove litter, as well as to change behaviour. So far, the effects of prevention policies have been ineffective, resulting in great amounts of litter at sea and suggesting that removal actions are needed. Between 2014 and 2016, 15 ports in five countries (Italy, Slovenia, Croatia, Montenegro and Greece) in the Adriatic-Ionian macroregion implemented Fishing for Litter (FFL) pilot projects. The FFL scheme is a clean-up activity that aims to remove marine litter from the seafloor: fishing vessels collect marine litter that is caught in their nets during fishing activities and dispose of it on the quayside. This study investigates the barriers to implementing the FFL scheme in the Adriatic-Ionian macroregion. We prioritized the strengths, weaknesses, opportunities, and threats (SWOT) of the pilot projects in each country and compared the Adriatic-Ionian experience with that of the FFL initiatives in progress in Scotland since 2005 to achieve a comparative description and benefit from the lessons learnt. The lack of a comprehensive, holistic approach to marine litter management and an ambiguous bureaucracy with unclear definitions of the responsibilities are the main factors hampering the implementation of the FFL scheme in the Adriatic-Ionian macroregion. However, the increasing number of directives and strategies to address marine litter and the extensive public interest and media coverage represent opportunities to institutionalize the scheme as an effective clean-up strategy in the region. Highlights: In the Fishing for Litter scheme fishermen land marine litter caught in the nets. EU directives, international strategies and conventions promote Fishing for Litter. The fishery sector can have a significant role in removing marine litter. A specific overarching legislation to address marine litter is needed. A Fishing for Litter coordinator at the national or regional level should be appointed.